First record of Albunea occulta (Boyko) (Crustacea: Decapoda: Albuneidae) from the Andaman Islands, India - Marimuthu, P.; Kumaralingam, S.; Jayaraj, K.a.; Equbal, Jawed; Ganesh, T. (Zootaxa, 2015)
The anomuran crabs of the family Albuneidae Stimpson, 1858 are specialized forms, living buried in sand. Because of their preferred habitat, they are very rarely encountered, and thus have been poorly studied in general (Osawa & Fujita 2012). They are commonly called “Sand crabs” (Boyko 2002). Worldwide, the Albuneidae family currently includes 48 species belonging to nine genera (Boyko & McLaughlin 2010). Among these species, the present study reported Albunea occulta Boyko, 2002 as new record to Indian coastal regions particularly from Andaman Islands.